2006
DOI: 10.1086/503548
|View full text |Cite
|
Sign up to set email alerts
|

Detection of the Effect of Cosmological Large-Scale Structure on the Orientation of Galaxies

Abstract: Galaxies are not distributed randomly throughout space but are instead arranged in an intricate "cosmic web" of filaments and walls surrounding bubble-like voids. There is still no compelling observational evidence of a link between the structure of the cosmic web and how galaxies form within it. However, such a connection is expected on the basis of our understanding of the origin of galaxy angular momentum: disk galaxies should be highly inclined relative to the plane defined by the large-scale structure sur… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
153
3
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(170 citation statements)
references
References 25 publications
13
153
3
1
Order By: Relevance
“…Each spin vector is normalized to unity. Other authors chose to use just one (Lee & Erdogdu 2007) or both (Kashikawa & Okamura 1992;Varela et al 2012) spin vector simultaneously (as we do) or use some other approach to deal with this indeterminacy of the spin vectors of galaxies (Trujillo et al 2006;Slosar & White 2009). …”
Section: Observational Samples and Galaxy Spin Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each spin vector is normalized to unity. Other authors chose to use just one (Lee & Erdogdu 2007) or both (Kashikawa & Okamura 1992;Varela et al 2012) spin vector simultaneously (as we do) or use some other approach to deal with this indeterminacy of the spin vectors of galaxies (Trujillo et al 2006;Slosar & White 2009). …”
Section: Observational Samples and Galaxy Spin Vectorsmentioning
confidence: 99%
“…Navarro et al (2004) found that (spiral) galaxies in the supergalactic plane tend to spin with their spin axis in the supergalactic plane. Trujillo et al (2006) also found that spin axes of spiral galaxies are preferentially in the plane of the walls of cosmic voids, although this signal appears to be disputed by Slosar & White (2009) who found no alignment between spiral galaxies and void walls. If sitting in a cosmic filament, and Tempel & Libeskind (2013) used the SDSS to show that the short axes of elliptical galaxies tend to be perpendicular to the filament axis.…”
Section: Introductionmentioning
confidence: 99%
“…This has resulted in robust detections of various alignments: Brainerd (2005), Yang et al (2006), and Azzaro et al (2007) all found that satellite galaxies are preferentially distributed along the major axes of their host galaxies, Trujillo et al (2006) found that spiral galaxies located on the shells of large voids have rotation axes that lie preferentially on the void surface, and Pereira & Kuhn (2005) and Agustsson & Brainerd (2006a) noticed that satellite galaxies tend to be preferentially oriented toward the galaxy at the center of the halo.…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of galaxy evolution with respect to CW features is the correlation between the spin of galaxies and their filaments, as recently detected in the SDSS (Tempel, Stoica, and Saar, 2013;Trujillo, Carretero, and Patiri, 2006;Zhang et al, 2013). This result confirms the role played by the large scale dynamical environment in the evolution of galaxies.…”
Section: Galaxy Properties and Large Scale Structure Of The Universementioning
confidence: 86%
“…On the other hand, Darvish et al (2014) and Fadda et al (2008) found an increased SFR for galaxies in filaments compared to clusters. In recent years, a few studies have also started to investigate the CW in great detail, considering all the possible structures (clusters, filaments, walls, and voids) and studying the statistical distribution of galaxy properties with respect to the CW (Brouwer et al, 2016;Eardley et al, 2015;Martínez, Muriel, and Coenda, 2016).An important aspect of galaxy evolution with respect to CW features is the correlation between the spin of galaxies and their filaments, as recently detected in the SDSS (Tempel, Stoica, and Saar, 2013;Trujillo, Carretero, and Patiri, 2006;Zhang et al, 2013). This result confirms the role played by the large scale dynamical environment in the evolution of galaxies.…”
mentioning
confidence: 99%